Degradation of Hydrocarbons by Members of the Genus Candida II. Oxidation of n-Alkanes and 1-Alkenes by Candida lipolytica - Klug, M. J. (1967)
Candida lipolytica ATCC 8661 was grown in a mineral-salts hydrocarbon medium. n-Alkanes and 1-alkenes with 14 through 18 carbon atoms were used as substrates. Ether extracts of culture fluids and cells obtained from cultures grown on the various substrates were analyzed by thin-layer and gas-liquid chromatography. Analyses of fluids from cultures grown on n-alkanes indicated a predominance of fatty acids and alcohols of the same chain length as the substrate. In addition, numerous other fatty acids and alcohols were present. Analyses of saponifiable and nonsaponifiable material obtained from the cells revealed essentially the same products. The presence of primary and secondary alcohols, as well as fatty acids, of the same chain length as the n-alkane substrate suggested that attack on both the methyl and α-methylene group was occurring. The significance of these two mechanisms in the degradation of n-alkanes by this organism was not evident from the data presented. Analyses of fluids from cultures grown on 1-alkenes indicated the presence of 1,2-diols, as well as ω-unsaturated fatty acids, of the same chain length as the substrate. Alcohols present were all unsaturated. Saponifiable and nonsaponifiable material obtained from cells contained essentially the same products. The presence of 1,2-diols and ω-unsaturated fatty acids of the same chain length as the substrate from cultures grown on 1-alkenes indicated that both the terminal methyl group and the terminal double bond were being attacked.